Research-Survivor Formative Evaluation of San Francisco's Anti-Human Trafficking Task Forces, California, 2016-2018 - Lutnick, Alexandra ([Verlag nicht ermittelbar], 2023)
Research Triangle Institute (RTI) International, in partnership with MD Consulting, conducted a researcher-survivor-ally participatory process evaluation of the Task Force on Anti-Human Trafficking in San Francisco. The purpose of the Task Force is to review current efforts to improve the city's response to human trafficking and identify gaps in services for survivors. Participants include representatives from social service organizations, law enforcement, community-based organizations, philanthropic and advocacy groups, and concerned citizens. This study included an integrated, multi-level approach of community involvement. People who have experienced a severe form of human trafficking are represented at all levels of the research process, including that of co-principal investigator (co-PI), research assistants (RAs) and members of the Community Advisory Board (CAB). The goals of this evaluation were to evaluate components of task force implementation through a comprehensive process evaluation, conduct a secondary analysis of law enforcement data, and create a research infrastructure that supports the intellectual and career development of people who have experienced trafficking.